Synthesis of 1, 4:3, 6‐Dianhydrohexitols Diesters from the Palladium‐Catalyzed Hydroesterification Reaction. Issue 11 (10th September 2014) - Pruvost, Romain; Boulanger, Jérôme; Léger, Bastien; Ponchel, Anne; Monflier, Eric; Ibert, Mathias; Mortreux, André; Chenal, Thomas; Sauthier, Mathieu
Abstract The hydroesterification of alpha olefins has been used to synthesize diesters from bio‐based secondary diols: isosorbide, isomannide, and isoidide. The reaction was promoted by 0.2 % palladium catalyst generated in situ from palladium acetate/triphenylphosphine/para‐toluene sulfonic acid. Optimized reaction conditions allowed the selective synthesis of the diesters with high yields and the reaction conditions could be scaled up to the synthesis of hundred grams of diesters from isosorbide and 1‐octene with solvent‐free conditions.